Cutting-edge patient-specific surgical plates for computer-assisted mandibular reconstruction: The art of matching structures and holes in precise surgery - Liu, Renshun; Su, Yuxiong; Pu, Jingya; Zhang, Chunyu; Yang, Weifa (Frontiers in Surgery, 2023)
Objectives: Cutting-edge patient-specific surgical plates (PSSPs) are supposed to improve the efficiency, precision, and functional outcomes of mandibular reconstruction. This study characterized the premium role of PSSPs in precise surgery and explored their working principles in computer-assisted mandibular reconstruction (CAMR). Methods: The PSSPs-enhanced surgical precision was investigated through the model surgery and representative cases. Spatial deviations of reconstruction were characterized by comparing the reconstructed mandible with the virtually designed mandible. Working principles of PSSPs were distinguished by a review of evolving surgical techniques in CAMR. Results: In the model surgery, spatial deviations between the virtually planned mandible and the reconstructed mandible were 1.03 ± 0.43 mm in absolute distance deviation, 1.70 ± 1.26 mm in intercondylar length, and 1.86 ± 0.91 mm in intergonial length in the study group of PSSPs, significantly smaller than in the control group of conventional prebent surgical plates. Meanwhile, in the study group, distance deviations were 0.51 ± 0.19 mm in bone-plate distance and 0.56 ± 0.28 mm in drilled screw holes, indicating the art of matching structures and holes. The PSSPs-enhanced CAMR was further demonstrated in three representative cases of mandibular reconstruction. Finally, four primary techniques of CAMR were summarized based on a review of 8672 articles. The premium role of PSSPs was distinguished by the benefits of matching structures and holes. Conclusions: The PSSPs-enhanced surgical precision was verified through the model surgery and demonstrated in human surgery. Compared to other surgical techniques of CAMR, PSSPs contributed to the precise surgery by the art of matching structures and holes.